The Practicality Test Of Audio-Based Podcast Media For Online Learning - Dedi Supendra; Grahita Kusumastuti; Fitri Maiziani; Elsa Rahmayanti (SPEKTRUM: Jurnal Pendidikan Luar Sekolah (PLS), 2022)
The outbreak of Covid-19 pandemic has been given an impatful consequence to the change of learning system from conventional to virtual meeting. The learning resources, at the beginning, are delivered by the teachers directly in the classroom and textbooks then become ineffective ways because the distance issue between the teachers and the students. Furthermore, a variety of digital based learning media then is developed, including implementing the Podcast in the learning and teaching process. This study aims at analyzing the practicality test of Podcast in Introduction to Education Course. About 121 students were involved to participate in giving their perspectives and opinion toward the developed media. The test had been conducted three times, namely: individual test, small group test, and field test. From the examination, it can be concluded that the result of individual test is enough practical with 78,6%, small group test is practical (83,3%) and field test is practical (88,4%). In the meantime, the students gave some positive reason on applying Podcast in learning, such as: the accessibily, flexibility, and the connectivity.